Common features of environmentally and socially engaged community programs addressing the intersecting challenges of planetary and human health: mixed methods analysis of survey and interview evidence from creative health practitioners - Thomson, Linda J. M.; Critten, Ailsa; Hume, Victoria; Chatterjee, Helen J. (Frontiers in Public Health, 2025)
Depending on environmental and social determinants, planetary health impacts unequally on human health. As it is likely that creativity and culture are under-tapped resources, the potential to address community and environmental issues to tackle health inequalities, especially those resulting from climate injustice, has not yet been fully realized. The study aimed to identify common features of environmentally and socially engaged UK community programs addressing the intersecting challenges of planetary and human health. A short survey was used to screen participants for in-depth semi-structured interviews. Inclusion criteria comprised adult practitioners offering environmentally and socially engaged community programs of creative and cultural activities leading to health and environmental outcomes. Thematic analysis of 19 surveys and eight interviews identified 146 responses, from which 12 themes with 98 subthemes were derived. Seventy per cent of responses were distributed across five major themes: ‘Collaboration and partnerships’, ‘Community health and wellbeing’, ‘Connection to nature’, ‘Funding’ and ‘Mental health’. Within these five themes, 10 subthemes which resulted from three or more similar responses by different participants were deemed common features of community programs. Two of the 10 subthemes: ‘Connection to nature in children’ and ‘Relationship with natural world’ within the major theme: ‘Connection to nature’ addressed planetary and human health directly through practices recognizing environmental and human interdependency. Four of the 10 subthemes: ‘Influencing wider systems’ within the major theme ‘Collaboration and partnerships’; and ‘Looking after our staff’, ‘Preventative measures’ and ‘Research evidence’ within the major theme ‘Mental health’; addressed planetary and human health indirectly through practitioner partnership influence over policies relating to climate change and by addressing concern for the environment manifesting in eco-anxiety. The study indicates the need for inclusive practice, partnership work, and sustainable funding that can support practitioner wellbeing and the process, outputs and impacts of natural and sustainable environment-based health interventions and other resources instrumental in preventative healthcare.